1990
DOI: 10.1590/s0036-46651990000100007
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of antibody to human parvovirus B19 in Rio de Janeiro, Brazil

Abstract: During 1985 and 1986 serum samples were collected from the Rio de Janeiro population and examined for the presence of IgG antibody to human parvovirus B19. No difference in prevalence was found between males and females. Antibody prevalence rose from 35% in children less than five years old to almost 80% in children aged eleven to fifteen years. The antibody prevalence in individuals over 50 years old was over 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
27
0
12

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 18 publications
9
27
0
12
Order By: Relevance
“…Although some studies (Freitas et al 1988, 1993, Miranda et al 1989, Nascimento et al 1990, Cubel et al 1992, Mielle et al 1995 have been published in recent years, including preliminary results of the first year of this study (Oliveira et al 1996), clinical and epidemiological aspects of parvovirus B19 are still not widely documented in Brazil. By systematically gathering data on acute rash diseases over the years we disclosed a seasonal pattern of the infection in a mid-sized urban area.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although some studies (Freitas et al 1988, 1993, Miranda et al 1989, Nascimento et al 1990, Cubel et al 1992, Mielle et al 1995 have been published in recent years, including preliminary results of the first year of this study (Oliveira et al 1996), clinical and epidemiological aspects of parvovirus B19 are still not widely documented in Brazil. By systematically gathering data on acute rash diseases over the years we disclosed a seasonal pattern of the infection in a mid-sized urban area.…”
Section: Discussionmentioning
confidence: 81%
“…Notwithstanding, prevalence studies conducted by Nascimento et al (1990), Freitas et al (1993Freitas et al ( , 1999 have shown that the infection is widespread in some states of the country.…”
mentioning
confidence: 98%
“…It is also lower than that in Brazil [13,14] and Africa [15]. On the other hand, antibody prevalence in adults over 35 years of age in Singapore was higher than that in Germany and a little lower than that in England and Wales and Japan (Fig.…”
mentioning
confidence: 86%
“…A serological survey of the Rio de Janeiro population showed that 30 to 60% of women of childbearing age have antibodies (Nascimento et al 1990) and thus at least 40% of women are still susceptible to infection during pregnancy. A previous study of hydrops fetalis done by the Pathology Department of the Instituto Fernandes Figueira (IFF/FIOCRUZ) during 1954 to 1992 showed that infectious diseases predominate over immunologic causes in the aetiology of hydrops fetalis (Garcia et al 1995).…”
mentioning
confidence: 99%